Social Interest dan Relevansinya Terhadap Keterlibatan Indonesia dalam G-20 - Sonideritus Bandung (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2022)
The purpose of this study is to discuss the theory of social interest which was coined by Adler. Adler believes that social interest is an attitude of interest that comes from within to connect with other people. The attitude of interest is manifested in the form of cooperation for social interests and social progress. Apparently, this fact reaffirms the existence of humans as social beings. Adler's theory of social interest is correlated with Indonesia's involvement in the G-20 international forum. The G-20 is a cooperation forum involving 19 major countries and the European Union in overcoming important issues such as climate issues, multilateral trade, and the global economic crisis due to the Covid-19 pandemic. Indonesia's participation in the G-20 forum presupposes Indonesia's commitment and contribution to promote mutual prosperity. The method used inthis study is the library research. The results found that humans cannot walk alone. They always need someone else. They must have the desire to take part, share and cooperate with othesr. The process of opening up, establishing relationships, and taking part in community is the first step for humans to achieve mutual prosperity